The Effect of Crude Oil Prices on Inflation, Interest Rates and Economic Growth in Indonesia - Rostin, Rostin; Muthalib, Abd Azis; Adam, Pasrun; Nur, Muh.; Saenong, Zainudin; Suriadi, La Ode; Baso, Jamal Nasir (International Journal of Energy Economics and Policy, 2019)
This study aims to examine the effect of crude oil prices on inflation, interest rates, and economic growth in Indonesia. The data used are quarterly time series data on crude oil, interest rates, inflation, and Indonesia’s economic growth from the first quarter of year 2001 to the second quarter of year 2017. To test the effect, an autoregressive distributed lag (ARDL) equations system or a multivariate ARDL model is used. The results of data analysis reveal that (1) there are no long-run and short-run effects of crude oil prices on inflation, (2) there are long-run and short-run effects of crude oil prices to the interest rate. In the long run, every 1% increase in the price of crude oil, the interest rate drops 0,26%, and (3) there is no effect of crude oil prices on economic growth both in the short and long-run. Keywords: crude oil prices, interest rate, inflation, economic growth, ARDL model. JEL Classifications: E300, E310, E42, O440 DOI: https://doi.org/10.32479/ijeep.7829